Micro‐Refuges or Ecological Traps: Context‐Dependent Effects of Rock Pools on Intertidal Biodiversity Across Latitudes - Louise B. Firth; Andrea Desiderato; Antony M. Knights; J. David Aguirre; Juan C. Astudillo; Juan C. Azofeifa‐Solano; David T. Bilton; Su Yin Chee; Hartvig C. Christie; Ronaldo A. Christofoletti; Amelia Curd; Katherine A. Dafforn; et al. (Global Ecology and Biogeography, 2026)
Aim We investigated how local‐scale environmental heterogeneity influences biodiversity patterns across broad biogeographic gradients, using intertidal microhabitats as a model system within one of the most environmentally stressful ecosystems on Earth. Location Intertidal habitats at 26 locations (two rocky shore sites per location) across six continents, spanning 98° of latitude (38°S to 60°N). Time Period 2019–2022. Major Taxa Studied Algae, sessile and mobile invertebrates. Methods We compared biodiversity and thermal environments across contrasting microhabitats (rock pools and adjacent emergent rock) along a latitudinal gradient, sampling during environmentally ‘milder’ and ‘harsher’ periods. Biodiversity was quantified using multiple richness metrics (mean, total, unique taxa) and functional diversity. Results Microhabitat differences strongly influenced biodiversity patterns across latitude. Rock pools consistently supported higher taxonomic and functional diversity than emergent rock, irrespective of sampling period, reflecting their ability to buffer thermal extremes, particularly under harsher conditions. Mean species richness exhibited a non‐linear, s‐shaped latitudinal pattern, with lowest values near the equator and higher richness at mid‐latitudes, diverging from classical Latitudinal Diversity Gradient expectations. Biodiversity differences between microhabitats were greatest in temperate regions and diminished at low latitudes, where extreme conditions constrained diversity across habitats. Main Conclusions Local environmental heterogeneity can substantially modify, and in some cases obscure large‐scale biodiversity patterns. By mediating exposure to environmental stress, intertidal microhabitats provide insight into how fine‐scale variability interacts with latitudinal stress gradients to shape biodiversity distributions. Incorporating microhabitat variability into biogeographic frameworks is important for understanding global biodiversity patterns and predicting ecological responses to climate change.

Modelling climatic variable impacts on ground-level ozone in Malaysia using backward trajectory and Generative Additive Models - F. P. Chee; M. C.-G. Ooi; Y. J. Wong; J. Sentian; J. Dayou; M. T. Latif; J. H.-W. Chang (International Journal of Environmental Science and Technology, 2025)

A review on the use of cellulose nanomaterials for wastewater remediation of heavy metal ions - T. Marimuthu; C. Y. Chee; N. M. N. Sulaiman (International Journal of Environmental Science and Technology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

A global analysis of complexity–biodiversity relationships on marine artificial structures - Elisabeth M. A. Strain; Peter D. Steinberg; Maria Vozzo; Emma L. Johnston; Marco Abbiati; Moises A. Aguilera; Laura Airoldi; J. David Aguirre; Gail Ashton; Maritina Bernardi; Paul Brooks; Benny K. K. Chan; et al. (Global Ecology and Biogeography, 2021)
Aim Topographic complexity is widely accepted as a key driver of biodiversity, but at the patch‐scale, complexity–biodiversity relationships may vary spatially and temporally according to the environmental stressors complexity mitigates, and the species richness and identity of potential colonists. Using a manipulative experiment, we assessed spatial variation in patch‐scale effects of complexity on intertidal biodiversity. Location 27 sites within 14 estuaries/bays distributed globally. Time period 2015–2017. Major taxa studied Functional groups of algae, sessile and mobile invertebrates. Methods Concrete tiles of differing complexity (flat; 2.5‐cm or 5‐cm complex) were affixed at low–high intertidal elevation on coastal defence structures, and the richness and abundance of the colonizing taxa were quantified after 12 months. Results The patch‐scale effects of complexity varied spatially and among functional groups. Complexity had neutral to positive effects on total, invertebrate and algal taxa richness, and invertebrate abundances. However, effects on the abundance of algae ranged from positive to negative, depending on location and functional group. The tidal elevation at which tiles were placed accounted for some variation. The total and invertebrate richness were greater at low or mid than at high intertidal elevations. Latitude was also an important source of spatial variation, with the effects of complexity on total richness and mobile mollusc abundance greatest at lower latitudes, whilst the cover of sessile invertebrates and sessile molluscs responded most strongly to complexity at higher latitudes. Conclusions After 12 months, patch‐scale relationships between biodiversity and habitat complexity were not universally positive. Instead, the relationship varied among functional groups and according to local abiotic and biotic conditions. This result challenges the assumption that effects of complexity on biodiversity are universally positive. The variable effect of complexity has ramifications for community and applied ecology, including eco‐engineering and restoration that seek to bolster biodiversity through the addition of complexity.

Betanodavirus : Dissection of the viral life cycle - C‐F Low; B Syarul Nataqain; H‐Y Chee; M Z H Rozaini; M Najiah (Journal of Fish Diseases, 2017)
Progressive research has been recently made in dissecting the molecular biology of Betanodavirus life cycle, the causative pathogen of viral encephalopathy and retinopathy in economic important marine fish species. Establishment of betanodavirus infectious clone allows the manipulation of virus genome for functional genomic study, which elucidates the biological event of the viral life cycle at molecular level. The betanodavirus strategizes its replication by expressing anti‐apoptosis/antinecrotic proteins to maintain the cell viability during early infection. Subsequently utilizes and controls the biological machinery of the infected cells for viral genome replication. Towards the late phase of infection, mass production of capsid protein for virion assembly induces the activation of host apoptosis pathway. It eventually leads to the cell lysis and death, which the lysis of cell contributes to the accomplishment of viral shedding that completes a viral life cycle. The recent efforts to dissect the entire betanodavirus life cycle are currently reviewed.

Streptococcus agalactiae outbreaks in cultured golden pomfret, Trachinotus blochii (Lacépède), in Singapore - S M Chong; W K Wong; W Y Lee; Z B Tan; Y H Tay; X H Teo; L D Chee; C J Fernandez (Journal of Fish Diseases, 2017)

Identification of immune response‐related genes and signalling pathways in spleen of Vibrio parahaemolyticus ‐infected Epinephelus fuscoguttatus (Forskal) by next‐generation sequencing - C‐F Low; N S Mariana; A Maha; H‐Y Chee; M Y Fatimah (Journal of Fish Diseases, 2016)

Non‐immune‐related genes and signalling pathways in spleen of Vibrio parahaemolyticus ‐infected Epinephelus fuscoguttatus (Forskal) - C‐F Low; N S Mariana; A Maha; H‐Y Chee; M Y Fatimah (Journal of Fish Diseases, 2015)

Experimental infection of brown‐marbled grouper, E pinephelus fuscoguttatus (Forskal), with V ibrio parahaemolyticus identifies parvalbumin beta‐2 subunit I, alpha‐2‐macroglobulin, nattectin and immunoglobulin light chain, differentially expressed in resistant grouper - C‐F Low; M Nor Shamsudin; M Abdullah; H‐Y Chee; M Aliyu‐Paiko (Journal of Fish Diseases, 2015)
The mechanisms through which brown‐marbled grouper accomplishes resistance to infection, particularly against Vibrios , are not yet fully understood. In this study, brown‐marbled grouper fingerlings were experimentally infected with Vibrio parahaemolyticus, to identify disease resistance grouper, and the serum proteome profiles were compared between resistant and susceptible candidates, via two‐dimensional gel electrophoresis (2‐ DE ). The results showed that putative parvalbumin beta‐2 subunit I, alpha‐2‐macroglobulin, nattectin and immunoglobulin light chain proteins were among proteins that significantly overexpressed in the resistant fish as compared to the susceptible group of fish, whereas apolipoprotein E and immunoglobulin light chain proteins were observed to be differentially overexpressed in the susceptible fish. Further analysis by peptide sequencing revealed that the immunoglobulin light chain proteins identified in the resistant and susceptible groups differed in amino acid composition. Taken together, the results demonstrated for the first time that putative parvalbumin beta‐2 subunit I, alpha‐2‐macroglobulin, nattectin and immunoglobulin light chain are among important proteins participating to effect disease resistance mechanism in fish and were overexpressed to function collectively to resist V. parahaemolyticus infection. Most of these molecules are mediators of immune response.

Putative apolipoprotein A‐I, natural killer cell enhancement factor and lysozyme g are involved in the early immune response of brown‐marbled grouper, Epinephelus fuscoguttatus, Forskal, to Vibrio alginolyticus - C‐F Low; M N Shamsudin; H‐Y Chee; M Aliyu‐Paiko; E S Idrus (Journal of Fish Diseases, 2014)
The gram‐negative bacterium, Vibrio alginolyticus , has frequently been identified as the pathogen responsible for the infectious disease called vibriosis. This disease is one of the major challenges facing brown‐marbled grouper aquaculture, causing fish farmers globally to suffer substantial economic losses. The objective of this study was to investigate the proteins involved in the immune response of brown‐marbled grouper fingerlings during their initial encounter with pathogenic organisms. To achieve this objective, a challenge experiment was performed, in which healthy brown‐marbled grouper fingerlings were divided into two groups. Fish in the treated group were subjected to intraperitoneal injection with an infectious dose of V. alginolyticus suspended in phosphate‐buffered saline ( PBS ), and those in the control group were injected with an equal volume of PBS . Blood samples were collected from a replicate number of fish from both groups at 4 h post‐challenge and analysed for immune response‐related serum proteins via two‐dimensional gel electrophoresis. The results showed that 14 protein spots were altered between the treated and control groups; these protein spots were further analysed to determine the identity of each protein via MALDI ‐ TOF / TOF . Among the altered proteins, three were clearly overexpressed in the treated group compared with the control; these were identified as putative apolipoprotein A‐I, natural killer cell enhancement factor and lysozyme g. Based on these results, these three highly expressed proteins participate in immune response‐related reactions during the initial exposure (4 h) of brown‐marbled grouper fingerling to V. alginolyticus infection.

Quantitative T-cell interferon-gamma responses to Mycobacterium tuberculosis-specific antigens in active and latent tuberculosis - C. B. E. Chee; T. M. S. Barkham; K. W. KhinMar; S. H. Gan; Y. T. Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Fusion of coregistered cross-modality images using a temporally alternating display method - J. S. Lee; B. Kim; Y. Chee; C. Kwark; M. C. Lee; K. S. Park (Medical & Biological Engineering & Computing, 2000)